2012 IEEE International Conference on Condition Monitoring and Diagnosis 2012
DOI: 10.1109/cmd.2012.6416402
|View full text |Cite
|
Sign up to set email alerts
|

Recent progress of CMD research and applications in China

Abstract: Accompanying with the significant development of power industry, condition monitoring and diagnosis (CMD) for power apparatus is developing rapidly in China in recent years. This paper introduces the recent progress of CMD research and applications in China, including field applications of CMD to power substation and power transmission lines by on-line monitoring and on-site detecting devices, the novel sensors and technologies developed, and CMD standards established in China. The problems of the existing CMD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Studies have found [20] that in the process of inducing atherosclerosis, inflammatory cytokines, such as VEGF and TNF-α, will induce the formation of vascular thrombosis and lead to a large number of normal apoptosis to aggravate the development of the disease in hyperlipidemia. Clinically, inflammatory factors such as IL6 and TNF-α in the TNF signaling pathway have become important indicators to measure the development of hyperlipidemia, and TNF-α and IL 6 can further accelerate the synthesis of Triglyceride(TG) by stimulating the liver [21,22]. Insulin resistance is closely related to hyperlipidemia [23].…”
Section: Analysis On the Health Care Mechanism Of Crataegi Fructus In...mentioning
confidence: 99%
“…Studies have found [20] that in the process of inducing atherosclerosis, inflammatory cytokines, such as VEGF and TNF-α, will induce the formation of vascular thrombosis and lead to a large number of normal apoptosis to aggravate the development of the disease in hyperlipidemia. Clinically, inflammatory factors such as IL6 and TNF-α in the TNF signaling pathway have become important indicators to measure the development of hyperlipidemia, and TNF-α and IL 6 can further accelerate the synthesis of Triglyceride(TG) by stimulating the liver [21,22]. Insulin resistance is closely related to hyperlipidemia [23].…”
Section: Analysis On the Health Care Mechanism Of Crataegi Fructus In...mentioning
confidence: 99%